A Critical Study of the Relationship Between Car Accidents and the Amount of Compensation Paid by the Insurance Company for the Period From 2016 Into 2020 - Zainab Khalil Hashem (Peerian Journals Publishing, 2022)
This research aims to critically study the relationship between the number of road accidents and the amount of compensation paid by the insurance company (compulsory insurance) for the period from 2016 into 2020. Traffic accidents are among the most prominent contemporary problems. It leads to human and material losses. Therefore, the result is economic losses which have an impact on the size of compensation paid by the company as compulsory insurance and does not require a document and that everyone is covered by compensation according to the conditions mentioned in the compulsory car insurance law (CCIL). The main research hypothesis states the existence of a relationship between the number of accidents and the amount of compensation paid. The selection of the research was based on the increase of road accidents for various reasons, with the scarcity of studies that address the relationship between this increase and the amount of compensation paid. The research reached a comparison, analysis and criticism of the variables over a five-year period based on traffic accident statistics recorded by the Iraqi transport and communications statistics directorate.
Keywords: Compulsory; insurance law; road accidents